U.S. Bank Behavior in the Wake of the 2007-2009 Financial Crisis - Hakura, Dalia; Barajas, Adolfo; Chami, Ralph; Cosimano, Thomas (Washington, D.C. : International Monetary Fund, 2010)
The paper examines the slowdown of lending by large U.S. banks over the period 2007Q3 - 2009Q2, focusing on: (i) whether capital or liquidity was the binding constraint; (ii) factors influencing banks' decision to hold capital; and (iii) their pricing behavior. Using quarterly data for the largest U.S. banks, the paper finds that capital, rather than liquidity, constrained lending. Banks took actions to increase capital by slowing lending and raising profit margins, not fully passing through the Federal Reserve's interest rate cuts. Banks optimally choose capital based on the expected future demand for loans and the marginal cost of capital.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet